Martensitic stainless steel flux-cored wire and preparation method of structural member
Through the combination of arc additive manufacturing technology and martensite stainless steel flux-core welding wire, the problem that traditional manufacturing methods are difficult to meet the needs of aircraft high-performance materials is solved, and high-performance aircraft landing gear structural parts are achieved.
Patent Information
- Application Number
- CN202411880047.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-19
AI Technical Summary
Traditional manufacturing methods are difficult to meet the demand for high-performance materials in modern aircraft, especially in terms of lightweight, high strength and corrosion resistance.
Arc additive manufacturing technology is used combined with martensite stainless steel flux-core welding wire, and additive manufacturing is carried out through MIG welding as a heat source to prepare high-performance aircraft landing gear structural parts.
It has achieved efficient manufacturing of high-performance martensite stainless steel structural parts, meeting the requirements of aircraft landing gear, and has good mechanical properties and corrosion resistance.
Smart Images

Figure CN119609454A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of welding wire materials, and in particular relates to a martensitic stainless steel flux-cored welding wire, and also relates to a method for preparing a structural part by using the martensitic stainless steel flux-cored welding wire. Background Art
[0002] With the continuous development of the aviation industry, the performance requirements for aircraft landing gear are getting higher and higher, especially in terms of light weight, high strength and corrosion resistance. Traditional manufacturing methods can no longer meet the needs of modern aircraft for high-performance materials.
[0003] Wire Arc Additive Manufacturing (WAAM) is a method of manufacturing complex structures by melting metal wires through an arc and depositing them layer by layer. First of all, the high deposition efficiency of WAAM technology is a notable feature. By using an arc as a heat source, WAAM can achieve a very high deposition rate, usually reaching a material deposition rate of several kilograms to tens of kilograms per hour, which is much higher than traditional laser additive manufacturing technology. This high deposition rate greatly shortens the manufacturing time and improves production efficiency. Secondly, WAAM technology also performs well in terms of cost-effectiveness. Since the equipment used by WAAM is mainly welding equipment, which is relatively mature and reasonably priced, the initial investment and operating costs of the equipment are relatively low. Compared with expensive laser systems, WAAM technology has obvious advantages in equipment cost and maintenance cost, making this technology particularly suitable for industrial fields that require large-scale production. In addition, WAAM technology also has high flexibility, and can achieve precise manufacturing of complex shapes by adjusting welding parameters and paths. This flexibility and large-scale manufacturing capabilities make WAAM technology an ideal choice for many high-demand industrial fields.
[0004] Martensitic stainless steel has high strength, excellent corrosion resistance, good processing performance, good weldability and processability, and is widely used in the aerospace field. Flux-cored welding wire is widely used in the field of additive manufacturing because it can flexibly adjust alloy elements and has higher cladding efficiency than solid welding wire.
[0005] By combining the advantages of arc additive manufacturing technology, precipitation hardening martensitic stainless steel properties and flux-cored welding wire, it is possible to manufacture high-performance aircraft landing gear and meet the modern aviation industry's needs for lightweight, high strength and corrosion resistance. With the continuous advancement of technology, arc additive manufacturing of aircraft landing gear precipitation hardening martensitic stainless steel flux-cored welding wire will show its wide application prospects in the aviation industry. The advancement of this technology will promote the development of the aviation industry and realize the efficient manufacturing of high-performance aircraft landing gear. Summary of the invention
[0006] The first object of the present invention is to provide a martensitic stainless steel flux-cored welding wire, which can be used as a raw material for additive manufacturing of martensitic stainless steel. The preparation process of the flux-cored welding wire is simple and pollution-free, and the composition is easy to control.
[0007] The second object of the present invention is to provide a method for preparing a structural part using a martensitic stainless steel flux-cored welding wire, wherein the method can be used for additive manufacturing of aircraft landing gear structural parts.
[0008] The first technical solution adopted by the present invention is: a martensitic stainless steel flux-cored welding wire, comprising a flux core and an outer sheath, wherein the flux core is composed of the following components by mass percentage: 12-15% chromium powder, 2-4% titanium powder, 6-8% molybdenum powder, 2-4% vanadium powder, 1-3% niobium powder, 0.2% carbon powder, 0.5-1% tungsten carbide, 1-2% manganese powder, 0.3-0.6% silicon powder, 0.1-0.2% rare earth oxide, and the rest is iron powder; The outer skin is 0Cr18Ni9 austenitic stainless steel strip, and the filling amount of the core powder is 23wt%-26wt%.
[0009] The second technical solution adopted by the present invention is: a method for preparing a structural part using a martensitic stainless steel flux-cored welding wire, which is specifically carried out according to the following steps: Step 1, weigh the following raw materials according to mass percentage: chromium powder 12-15%, titanium powder 2-4%, molybdenum powder 6-8%, vanadium powder 2-4%, niobium powder 1-3%, carbon powder 0.2%, tungsten carbide 0.5-1%, manganese powder 1-2%, silicon powder 0.3-0.6%, rare earth oxide 0.1-0.2%, and the rest is iron powder; Step 2: heating and keeping the raw material powder weighed in step 1 in an inert gas atmosphere to remove moisture; Step 3, placing the outer skin on the unwinding machine of the welding wire forming machine, rolling the outer skin into a U-shaped groove through the pressing groove of the forming machine, keeping the raw material powder obtained in step 2 warm and then cooling it to room temperature with the furnace, then filling the powder into the U-shaped groove, the filling rate of the flux core powder is controlled at 23wt%-26wt%, and after closing the forming rollers, a 2.10mm welding wire is made, and a 1.20mm flux cored welding wire is finally made by a step-by-step reduction method; Step 4: Assemble the prepared flux-cored welding wire onto the fully automatic welding robot, and use MIG welding as the heat source to perform additive manufacturing to obtain the structural parts. As the welding head moves, the molten metal accumulates layer by layer on the substrate, and the thickness of each layer is usually controlled at 2-3 mm, which can ensure the stability of the deposited layer and the density of the structure. The welding path is precisely controlled by a pre-programmed robot system, and the robot can weld according to the set trajectory to ensure that the shape and size of each layer meet the design requirements. In the process of additive manufacturing, the layers need to be well combined, which requires the temperature between the layers to be controlled during the welding process. The temperature between the layers is fixed at 100-150 ° C to avoid deformation or cracks caused by excessive heat accumulation. Finally, after completing the arc additive manufacturing, the structural parts may need to be processed later, such as removing welding slag and grinding the surface to obtain the final product.
[0010] The present invention adopts the second technical solution, which is characterized in that: In step 3, the inert protective atmosphere is argon gas with a purity of 99.999%; In step 3, the outer skin is a 0Cr18Ni9 austenitic stainless steel strip.
[0011] In step 2, the heating temperature is 150-200° C. and the insulation time is 2-2.5 h.
[0012] In step 4, the process parameters of MIG welding are welding speed 0.2m / min-0.3m / min; the welding gun is lifted 2mm-3mm per layer, and the shielding gas is argon with a purity of 99.999%; The third technical solution adopted by the present invention is that the martensitic stainless steel structural part is prepared by the above method.
[0013] The beneficial effects of the present invention are: 1. The martensitic stainless steel flux-cored welding wire of the present invention has a short preparation cycle and high production efficiency. The performance can be improved by adjusting the flux core composition and proportion. At the same time, the flux-cored welding wire is pollution-free in production and has high cladding efficiency during the welding process.
[0014] 2. The strengthening effect of the martensitic stainless steel flux-cored welding wire of the present invention is that a variety of precipitated phase elements are added to the welding wire, Cr and Ni elements are used as main alloy components, a certain amount of trace alloy elements such as V, Mo, Nb, Ti, as well as WC hard phase and a small amount of rare earth oxides are added, and the proportion of each element is strictly controlled, thereby obtaining a martensitic stainless steel flux-cored welding wire with excellent performance.
[0015] 3. The present invention discloses a method for preparing a structural part by using a flux-cored welding wire for martensitic stainless steel, and a method for preparing martensitic stainless steel by using an additive manufacturing technology with MIG welding as a heat source and flux-cored welding wire as a raw material; the present invention places a uniformly mixed flux-cored powder in a tubular furnace, continuously introduces argon gas, and keeps the temperature at 150°C to 200°C for 2h to 2.5h; the present invention uses fully automatic welding robot programming to realize additive manufacturing of martensitic stainless steel structural parts with high efficiency; the arc is stable during the printing process, the weld is beautifully formed, the surface is smooth, the burrs are only 2-3mm, and there are no pores or slag inclusions.
[0016] 4. The martensitic stainless steel structural parts obtained by additive manufacturing of the present invention have beautiful shape and excellent mechanical properties, and perfectly meet the use requirements of aircraft landing gear. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a stress-strain curve diagram of the martensitic stainless steel prepared by the flux-cored welding wire in Example 5 of the present invention.
[0018] Figure 2 This is a microstructure diagram of a martensitic stainless steel structural component prepared in Example 5 of the present invention. DETAILED DESCRIPTION
[0019] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0020] Example 1 The invention provides a martensitic stainless steel flux-cored welding wire, comprising a flux core and a sheath, wherein the flux core consists of the following components in percentage by mass: 12-15% chromium powder, 2-4% titanium powder, 6-8% molybdenum powder, 2-4% vanadium powder, 1-3% niobium powder, 0.2% carbon powder, 0.5-1% tungsten carbide, 1-2% manganese powder, 0.3-0.6% silicon powder, 0.1-0.2% rare earth oxide, and the remainder is iron powder; the sheath is a 0Cr18Ni9 austenitic stainless steel strip, and the filling amount of the flux core powder is controlled to be 20wt%-25wt%.
[0021] The role and function of each component in the welding wire are as follows: Cr element: Cr element is a necessary element to improve corrosion resistance. During welding, Cr atoms generally have a strong affinity with C atoms. In a long-term high-temperature environment, C atoms will migrate to the high-Cr area to form a carbide aggregation area, which has a great tendency to harden in subsequent treatments. At the same time, Cr element is also a ferrite-forming element, which can reduce the Ms point; Ni element: Ni element mainly promotes the formation of austenite in the weld structure. Ni element will move the γ phase region toward the direction of higher Cr element to avoid too much ferrite in the weld. However, when the Ni content is too high, it will reduce the Ms point, making it difficult for martensite to transform in the structure, resulting in more residual austenite structure and reducing the strength of the weld metal; Mo element: Mo element can improve strength and corrosion resistance. Mo-rich phase precipitates during aging to improve weld strength. Mo can prohibit other precipitates in the weld metal from diffusing and precipitating at the grain boundary, avoiding intergranular fracture. The interaction between Mo and Cr can improve the corrosion resistance of the weld; Nb element: Both Nb and Ti have aging strengthening effects, but Nb has less effect on toughness than Ti. This is because Nb (C, N) precipitates at the grain boundaries, and the crystal still has a large deformation capacity, while Ti precipitates are evenly dispersed inside the grains, and the deformation capacity is weakened, resulting in a decrease in toughness.
[0022] Ti element: The strengthening effect of Ti element is mainly reflected in two aspects: fine grain strengthening and precipitation strengthening. The appropriate amount of Ti addition can serve as a nucleation site during the solidification process of the molten pool, promoting the refinement of the structure. The presence of a large number of fine grain boundaries can effectively hinder the movement of dislocations, thereby limiting deformation and crack propagation, and improving the yield strength and impact toughness of steel.
[0023] Mn and Si elements: During the welding process, the main functions of Mn and Si are deoxidation and desulfurization, which can reduce the content of oxygen and sulfur in the surfacing alloy and prevent defects such as pores from being generated in the surfacing metal, resulting in a decrease in forming quality.
[0024] WC element: As a high-strength hard phase, WC can not only serve as a nucleation point in the molten pool, thereby refining the grains and improving the strength of the material, but also can be precipitated to strengthen and thus improve the strength and toughness of martensitic stainless steel.
[0025] Rare earth elements (Re): Rare earth elements can combine with impurity elements in the weld to achieve a solid solution strengthening effect and increase strength. Re can increase the volume fraction of lath martensite in the weld metal, refine the grain size, reduce the proportion of retained austenite, and inhibit the generation of lamellar martensite, making carbides spheroidized and dispersed in the ferrite matrix. Re can modify impurities and purify grain boundaries, improving impact toughness. The present invention also provides a method for preparing a structural part by using a martensitic stainless steel flux-cored welding wire, which is specifically prepared according to the following steps: Step 1, weigh the following raw materials according to mass percentage: chromium powder 12-15%, titanium powder 2-4%, molybdenum powder 6-8%, vanadium powder 2-4%, niobium powder 1-3%, carbon powder 0.2%, tungsten carbide 0.5-1%, manganese powder 1-2%, silicon powder 0.3-0.6%, rare earth oxide 0.1-0.2%, and the rest is iron powder; Step 2: heating and keeping the raw material powder weighed in step 1 in an inert gas atmosphere to remove moisture; In step 2, the heating temperature is 150°C to 200°C, and the insulation time is 2h to 2.5h.
[0026] Step 3, placing the outer skin on the unwinding machine of the welding wire forming machine, rolling the outer skin into a U-shaped groove through the pressing groove of the forming machine, keeping the raw material powder obtained in step 2 warm and then cooling it to room temperature with the furnace, then filling the powder into the U-shaped groove, the filling rate of the flux core powder is controlled at 20wt%-25wt%, and after closing the forming rollers, a 2.10mm welding wire is made, and a 1.20mm flux cored welding wire is finally made by a step-by-step reduction method; In step 3, the inert atmosphere is argon gas with a purity of 99.999%; in step 3, the outer skin is a 0Cr18Ni9 austenitic stainless steel strip.
[0027] Step 4: Assemble the prepared flux-cored welding wire onto the fully automatic welding robot, and use MIG welding as the heat source to perform additive manufacturing to obtain the structural parts. The specific parameters of the welding process are: welding speed is 0.2m / min-0.3m / min; the welding gun is lifted by 2mm-3mm per layer; the shielding gas is 99.999% argon. As the welding head moves, the molten metal accumulates layer by layer on the substrate, and the thickness of each layer is usually controlled at 2-3 mm, which can ensure the stability of the deposited layer and the density of the structure. The welding path is precisely controlled by a pre-programmed robot system, and the robot can weld according to the set trajectory to ensure that the shape and size of each layer meet the design requirements. In the process of additive manufacturing, the layers need to be well combined, which requires the temperature between the layers to be controlled during the welding process. The temperature between the layers is fixed at 100-150℃ to avoid deformation or cracks caused by excessive heat accumulation. Finally, after completing the arc additive manufacturing, the structural parts may need to be processed later, such as removing welding slag and polishing the surface to obtain the final product.
[0028] Example 2 Step 1: Weigh 12% chromium powder, 2% titanium powder, 8% molybdenum powder, 2% vanadium powder, 1% niobium powder, 0.2% carbon powder, 0.5% tungsten carbide, 1% manganese powder, 0.6% silicon powder, 0.1% rare earth oxide, and the rest is iron powder, and the sum of the mass percentages of the above components is 100%; Step 2: Mix all the raw materials weighed in step 1 evenly and place them in a tube furnace. Keep the mixture at 200° C. for 2.5 h while continuously introducing argon.
[0029] Step 3: Place a 0Cr18Ni9 austenitic stainless steel strip (the composition is shown in Table 1) with a width of 7 mm and a thickness of 0.3 mm on the unwinding machine of the welding wire forming machine, roll the steel strip into a U-shaped groove through the pressing groove of the forming machine, put the flux core powder obtained in step 2 into the U-shaped groove, and control the filling rate of the flux core powder to 24wt%. Then, use the forming machine to roll and close the U-shaped groove, wipe it clean with acetone or anhydrous ethanol, and draw it into a welding wire with a diameter of 2.1 mm, then reduce the diameter to 1.20 mm, wipe the oil stains on the welding wire with a cotton cloth dipped in acetone or anhydrous ethanol, and finally straighten the welding wire through a wire drawing machine, coil it into a disc, and seal it to obtain a martensitic stainless steel flux cored welding wire for additive manufacturing.
[0030] Table 1 shows the chemical composition (mass fraction%) of the 0Cr18Ni9 austenitic stainless steel strip used.
[0031] Step 4: Load the prepared martensitic stainless steel flux-cored welding wire for additive manufacturing into the fully automatic welding robot, and use MIG welding as the heat source for additive manufacturing to obtain the structural parts. The specific parameters of the welding process are: welding speed is 0.2m / min-0.3m / min; the welding gun is lifted by 2mm-3mm for each layer; the shielding gas is 99.999% argon. As the welding head moves, the molten metal accumulates layer by layer on the substrate, and the thickness of each layer is usually controlled at 2-3 mm, which can ensure the stability of the deposited layer and the density of the structure. The welding path is precisely controlled by a pre-programmed robot system, and the robot can weld according to the set trajectory to ensure that the shape and size of each layer meet the design requirements. In the process of additive manufacturing, good bonding between layers is required, which requires the temperature between layers to be controlled during the welding process. The temperature between layers is fixed at 100-150℃ to avoid deformation or cracks caused by excessive heat accumulation. Finally, after completing arc additive manufacturing, the structural parts may need to be processed later, such as removing welding slag and grinding the surface to obtain the final product.
[0032] The martensitic stainless steel molded parts prepared in this example have beautiful molding, no obvious spatter, tensile strength up to 883.6MPa, and elongation of 10.5%.
[0033] Example 3 Step 1: Weigh 14% chromium powder, 2% titanium powder, 6.5% molybdenum powder, 3% vanadium powder, 1.5% niobium powder, 0.2% carbon powder, 0.6% tungsten carbide, 1.5% manganese powder, 0.5% silicon powder, 0.1% rare earth oxide, and the rest iron powder according to mass percentage; Step 2: Mix all the raw materials weighed in step 1 evenly and place them in a tube furnace. Keep the mixture at 200° C. for 2.5 h while continuously introducing argon.
[0034] Step 3: Place a 0Cr18Ni9 austenitic stainless steel strip (the composition is shown in Table 1) with a width of 7 mm and a thickness of 0.3 mm on the unwinding machine of the welding wire forming machine, and roll the steel strip into a U-shaped groove through the pressing groove of the forming machine. Put the flux core powder obtained in step 2 into the U-shaped groove, and the filling rate of the flux core powder is controlled at 23wt%. Then, the U-shaped groove is rolled and closed by the forming machine, and the welding wire with a diameter of 2.1 mm is wiped clean with acetone or anhydrous ethanol, and then reduced to 1.20 mm. Wipe the oil stains on the welding wire with a cotton cloth dipped in acetone or anhydrous ethanol, and finally straighten the welding wire through a wire drawing machine, coil it into a disc, and seal it to obtain a martensitic stainless steel flux cored welding wire for additive manufacturing.
[0035] Step 4: Load the prepared martensitic stainless steel flux-cored welding wire for additive manufacturing into the fully automatic welding robot, and use MIG welding as the heat source for additive manufacturing to obtain the structural parts. The specific parameters of the welding process are: welding speed is 0.2m / min-0.3m / min; the welding gun is lifted by 2mm-3mm for each layer; the shielding gas is 99.999% argon. As the welding head moves, the molten metal accumulates layer by layer on the substrate, and the thickness of each layer is usually controlled at 2-3 mm, which can ensure the stability of the deposited layer and the density of the structure. The welding path is precisely controlled by a pre-programmed robot system, and the robot can weld according to the set trajectory to ensure that the shape and size of each layer meet the design requirements. In the process of additive manufacturing, good bonding between layers is required, which requires the temperature between layers to be controlled during the welding process. The temperature between layers is fixed at 100-150℃ to avoid deformation or cracks caused by excessive heat accumulation. Finally, after completing arc additive manufacturing, the structural parts may need to be processed later, such as removing welding slag and grinding the surface to obtain the final product.
[0036] The martensitic stainless steel formed parts prepared in this example have good mechanical properties, no obvious splashing, a tensile strength of up to 915.2 MPa, and an elongation of 11.6%.
[0037] Example 4 Step 1: Weigh 13% chromium powder, 3% titanium powder, 8% molybdenum powder, 4% vanadium powder, 2.5% niobium powder, 0.2% carbon powder, 1% tungsten carbide, 1% manganese powder, 0.6% silicon powder, 0.15% rare earth oxide, and the rest is iron powder, and the sum of the mass percentages of the above components is 100%; Step 2: Mix all the raw materials weighed in step 1 evenly and place them in a tube furnace. Keep the mixture at 200° C. for 2.5 h while continuously introducing argon.
[0038] Step 3: Place a 0Cr18Ni9 austenitic stainless steel strip (the composition is shown in Table 1) with a width of 7 mm and a thickness of 0.3 mm on the unwinding machine of the welding wire forming machine, roll the steel strip into a U-shaped groove through the pressing groove of the forming machine, put the flux core powder obtained in step 2 into the U-shaped groove, and control the filling rate of the flux core powder at 26wt%. Then, use the forming machine to roll and close the U-shaped groove, wipe it clean with acetone or anhydrous ethanol, and draw it into a welding wire with a diameter of 2.1 mm, then reduce the diameter to 1.20 mm, wipe the oil stains on the welding wire with a cotton cloth dipped in acetone or anhydrous ethanol, and finally straighten the welding wire through a wire drawing machine, coil it into a disc, and seal it to obtain a martensitic stainless steel flux cored welding wire for additive manufacturing.
[0039] Step 4: Load the prepared martensitic stainless steel flux-cored welding wire for additive manufacturing into the fully automatic welding robot, and use MIG welding as the heat source for additive manufacturing to obtain the structural parts. The specific parameters of the welding process are: welding speed is 0.2m / min-0.3m / min; the welding gun is lifted by 2mm-3mm for each layer; the shielding gas is 99.999% argon. As the welding head moves, the molten metal accumulates layer by layer on the substrate, and the thickness of each layer is usually controlled at 2-3 mm, which can ensure the stability of the deposited layer and the density of the structure. The welding path is precisely controlled by a pre-programmed robot system, and the robot can weld according to the set trajectory to ensure that the shape and size of each layer meet the design requirements. In the process of additive manufacturing, good bonding between layers is required, which requires the temperature between layers to be controlled during the welding process. The temperature between layers is fixed at 100-150℃ to avoid deformation or cracks caused by excessive heat accumulation. Finally, after completing arc additive manufacturing, the structural parts may need to be processed later, such as removing welding slag and grinding the surface to obtain the final product.
[0040] The martensitic stainless steel formed parts prepared in this example have no cracks or pores on the surface, no obvious spatter during the welding process, and the tensile strength can reach 964.2 MPa and the elongation is 8.2%.
[0041] Example 5 Step 1: Weigh 16% chromium powder, 4% titanium powder, 7% molybdenum powder, 2% vanadium powder, 3% niobium powder, 0.2% carbon powder, 0.6% tungsten carbide, 2% manganese powder, 0.4% silicon powder, 0.2% rare earth oxide, and the rest is iron powder, and the sum of the mass percentages of the above components is 100%; Step 2: Mix all the raw materials weighed in step 1 evenly and place them in a tube furnace. Keep the mixture at 200° C. for 2.5 h while continuously introducing argon.
[0042] Step 3: Place a 0Cr18Ni9 austenitic stainless steel strip (the composition is shown in Table 1) with a width of 7 mm and a thickness of 0.3 mm on the unwinding machine of the welding wire forming machine, and roll the steel strip into a U-shaped groove through the pressing groove of the forming machine. Put the flux core powder obtained in step 2 into the U-shaped groove, and the filling rate of the flux core powder is controlled at 25wt%. Then, the U-shaped groove is rolled and closed by the forming machine, and the welding wire with a diameter of 2.1 mm is wiped clean with acetone or anhydrous ethanol, and then reduced to 1.20 mm. Wipe the oil stains on the welding wire with a cotton cloth dipped in acetone or anhydrous ethanol, and finally straighten the welding wire through a wire drawing machine, coil it into a disc, and seal it to obtain a martensitic stainless steel flux cored welding wire for additive manufacturing.
[0043] Step 4: Load the prepared martensitic stainless steel flux-cored welding wire for additive manufacturing into the fully automatic welding robot, and use MIG welding as the heat source for additive manufacturing to obtain the structural parts. The specific parameters of the welding process are: welding speed is 0.2m / min-0.3m / min; the welding gun is lifted by 2mm-3mm for each layer; the shielding gas is 99.999% argon. As the welding head moves, the molten metal accumulates layer by layer on the substrate, and the thickness of each layer is usually controlled at 2-3 mm, which can ensure the stability of the deposited layer and the density of the structure. The welding path is precisely controlled by a pre-programmed robot system, and the robot can weld according to the set trajectory to ensure that the shape and size of each layer meet the design requirements. In the process of additive manufacturing, good bonding between layers is required, which requires the temperature between layers to be controlled during the welding process. The temperature between layers is fixed at 100-150℃ to avoid deformation or cracks caused by excessive heat accumulation. Finally, after completing arc additive manufacturing, the structural parts may need to be processed later, such as removing welding slag and grinding the surface to obtain the final product.
[0044] The martensitic stainless steel components obtained in this embodiment have beautiful shape, and the macroscopic morphology shows that the deposited parts show obvious stratification, the metallurgical bonding between the layers is good, and there are no defects such as pores and inclusions. Figure 2 As shown, the microstructure is lath martensite structure + retained austenite structure + ferrite structure.
[0045] Example 6 Based on Example 5, In the process of additive manufacturing, the additive structure changes from δ-ferrite distributed on the austenite matrix to lath martensite. When the martensite in the weld structure is formed, a high-density lattice defect will be formed inside its crystal. The high-density dislocations in the lath martensite will play a role in pinning dislocations, making the martensite stronger. At the same time, after the transformation of austenite to martensite is completed, the C element and other elements in the weld metal will migrate and concentrate to the dislocations in the organization or to other lattice defects, hindering the movement of dislocations. When dislocations move, higher energy is required, which makes the martensite have high strength and improves the strength of additive manufacturing structural parts.
[0046] After mechanical properties testing, the stress-strain curve of stainless steel structural parts is as follows: Figure 1 As shown, the tensile strength of the molded part of this embodiment can reach 977.8MPa, and the elongation is 14.5%. In summary, the martensitic stainless steel obtained by the present invention has good mechanical performance indicators and fully meets the use requirements of aircraft landing gear.
[0047] The alloy powders such as Cr, V, and Nb added to the welding wire core of the present invention can all be combined with the C element to form carbides, thereby serving as a reinforcing phase to improve the performance of martensite. At the same time, the reinforcing phase is generated in situ, and its grains are finer, which can also improve the toughness of the martensitic structural parts. The proportion of the C element in martensitic stainless steel is more important. When the carbon element is less than 0.2%, it is lath martensite, which has better toughness. When it is greater than 1.0%, it is flaky martensite, which is more brittle and difficult to use in additive manufacturing. Therefore, the carbon content in the powder of the present invention is maintained at 0.2%. According to the powder coating rate of 25%, the C content of the present invention is below 0.2%. The addition of WC should not be too much. Excessive WC will cause the martensitic stainless steel additive manufacturing structural parts to crack during the additive process, but a small amount of addition can also serve as a very strong reinforcing phase to improve the mechanical properties and improve the mechanical properties and organization of the overall structural parts. A small amount of rare earth oxide addition can improve the fluidity of the overall metal powder and improve its fracture toughness and elongation.
Claims
1. Martensitic stainless steel flux-cored welding wire, characterized in that: The welding wire includes a flux core and an outer sheath. The flux core is composed of the following components in mass percentage: 12-15% chromium powder, 2-4% titanium powder, 6-8% molybdenum powder, 2-4% vanadium powder, 1-3% niobium powder, 0.2% carbon powder, 0.5-1% tungsten carbide, 1-2% manganese powder, 0.3-0.6% silicon powder, 0.1-0.2% rare earth oxide, and the rest is iron powder.
2. The martensitic stainless steel flux-cored welding wire according to claim 1, characterized in that: The outer skin is a 0Cr18Ni9 austenitic stainless steel strip, and the filling rate of the core powder is controlled at 23wt%-26wt%.
3. A method for preparing a structural part using a martensitic stainless steel flux-cored welding wire, characterized in that: The specific steps are as follows: Step 1, weighing 12-15% chromium powder, 2-4% titanium powder, 6-8% molybdenum powder, 2-4% vanadium powder, 1-3% niobium powder, 0.2% carbon powder, 0.5-1% tungsten carbide, 1-2% manganese powder, 0.3-0.6% silicon powder, 0.1-0.2% rare earth oxide, and the rest iron powder according to mass percentage; Step 2: heating the alloy powder weighed in step 1 in an inert gas atmosphere and keeping it warm for a period of time to remove moisture; Step 3, the alloy powder obtained in step 2 is kept warm and then cooled to room temperature with the furnace, and then the powder is filled into the U-shaped groove of the outer skin, and is made into a 2.10 mm welding wire after passing through a closed forming roller, and is made into a 1.20 mm flux-cored welding wire by a step-by-step reduction method; Step 4: Assemble the prepared flux-cored welding wire to the fully automatic welding robot, and use MIG welding as the heat source to perform additive manufacturing to obtain the structural parts; as the welding head moves, the molten metal accumulates layer by layer on the substrate, and the thickness of each layer is controlled at 2-3 mm to ensure the stability of the deposited layer and the density of the structure; the welding path is precisely controlled by the robot system, and welding is performed according to the set trajectory to ensure that the shape and size of each layer meet the design requirements; after completing the arc additive manufacturing, remove the welding slag from the structural parts and polish the surface to obtain the final product.
4. The method for preparing a structural part using a martensitic stainless steel flux-cored welding wire according to claim 3, characterized in that: In step 2, the heating temperature is 150-200° C. and the insulation time is 2-2.5 h.
5. The method for preparing a structural part using a martensitic stainless steel flux-cored welding wire according to claim 3, characterized in that: The inert atmosphere in step 3 is 99.999% argon.
6. The method for preparing a structural part using a martensitic stainless steel flux-cored welding wire according to claim 3, characterized in that: The outer skin in step 3 is a 0Cr18Ni9 austenitic stainless steel strip.
7. The method for preparing a structural part using a martensitic stainless steel flux-cored welding wire according to claim 3, characterized in that: In step 4, the process parameters of MIG welding are welding speed 0.2m / min-0.3m / min; the welding gun is raised 2mm-3mm for each layer, and the shielding gas is argon with a purity of 99.999%.
8. The method for preparing a structural part using a martensitic stainless steel flux-cored welding wire according to claim 3, characterized in that: Step 4 During the additive manufacturing process, the interlayer temperature is fixed at 100-150°C.
9. A structural part prepared by using a martensitic stainless steel flux-cored welding wire, characterized in that: A method for preparing a structural part using a martensitic stainless steel flux-cored welding wire as described in any one of claims 3 to 7.
Citation Information
Patent Citations
Flux-cored welding wire for X120 pipeline steel welding and manufacturing method thereof
CN104741816A
Flux-cored wires and method for preparing low-alloy steel / martensitic stainless steel structural part through same
CN112935631A
Titanium carbide high-crack-resistance surfacing flux-cored wire, and preparation method and application thereof
CN113977131A
Metal type flux-cored wire and martensitic stainless steel structural part additive preparation method
CN117415509A
Flux cored wire
RU2679372C1